STRATEGIC MANAGEMENT OF SCHOOL PRINCIPALS TO IMPROVE THE QUALITY OF ISLAMIC RELIGIOUS EDUCATION AT SD ALKAUTSAR TEMANGGUNG - Nurodin Usman; Purwaningsih Purwaningsih; Billy Eka Wardana; Nurhariyanti Nurhariyanti (Institute of Computer Science (IOCS), 2022)
This study aims to determine: (1) How to plan, (2) How to implement and (3) How to evaluate strategic management in improving the quality of schools at SD Alkautsar Temanggung. This research is a qualitative descriptive study, data collected through the methods of observation, interviews, documentation, triangulation, and analyzed using descriptive analysis techniques. This study aims to determine the process of planning, implementing, and evaluating strategic management in improving the quality of schools at SD Alkautsar Temanggung. In the study of strategic management in improving the quality of schools at SD Alkautsar Temanggung, it shows that: (1) strategic planning includes four activities, namely formulating the vision, mission, objectives, identify internal and external factors, determine superior strategies, and long-term planning. short, medium and long. From the results above, it can be concluded that the total employment of Short Term Program Indicators is 95%, Medium Term Program is 96.6%, and Long Term Program is 90%. (2) the implementation of strategic management at SD Alkautsar Temanggung includes policy determination, motivation of educators and education staff, allocation of human resources, and development of school culture. (3) Evaluation of strategic management includes monitoring of all planning and implementation results, measuring school performance and taking corrective steps